(untitled) (Research, Society and Development, 2022)
This article presents the preliminary results of a study based on the reading of the construction process of the nautical astrolabe instrument described by Simão d’Oliveira in his treatise entitled Arte de Navegar, published in 1606, with a view to contemplating some didactic potentialities for the teaching geometry. The hypothesis is raised that, through the reading of the manufacturing process of the nautical astrolabe associated with a teaching organization - based on the articulation between the context of the mathematical concepts that emerge from the original historical document and the movement of thought, linked to the formation of these conceptions - can lead the student in the classroom in a fruitful way to the development of the process of analysis and synthesis, of paramount importance to the conceptual formation. In this way, we verified that through the description of the nautical instrument construction process, it was possible to explore some geometric knowledge arising from some actions of the instrument’s manufacturing description, such as the concepts of circumference; diameter, bisector, angles, quadrant, perpendicularity, degrees, among others.